FISCAL STRESS: Studi Kasus Pemda Provinsi Nusa Tenggara Timur - Mesri Welhelmina N. Manafe; Zet Ena; Salmun Saul Adu (Akademi Akuntansi YKPN Yogyakarta, 2018)
Local governments play a significant role in the life of the community and the national economy which can be achieved in fiscal health conditions reflected in the low disparity in income structure towards regional expenditure. The inability of regions to escape fiscal dependence is due to the low income, especially from Pendapatan Asli Daerah, which causes fiscal stress which then impacts on policies and implementation of regional spending through spending on programs and activities. This study will examine the relationship between Fiscal Stress and Pendapatan Asli Daerah and expenditure of East Nusa Tenggara Province through simple linear regression testing using secondary data Pertumbuhan Pendapatan Asli Daerah and Belanja Langsung using a sample of six (6) districts / cities in 2014-2016 The results of the study show that the fiscal stress variable does not affect the income structure through Pertumbuhan Pendapatan Asli Daerah and Belanja Langsung at a significance level of <0.05. The results of this study contribute to local budget policies and theoretically to the use of direct expenditure variables that are different from previous studies. Key Words: Fiscal Health, Fiscal Stress, Pendapatan Asli Daerah, dan Belanja Langsung